The Application of Cold-Induced Liquid–Liquid Extraction for the Determination of 4-Methylimidazole in Tea and Associated Risk Assessment for Chinese Tea Consumers - Shaohua Li; Lian Wang; Dawei Chen; Hong Li (Toxics, 2023)
4-Methylimidazole (4-MEI), as a Maillard reaction product, often occurs in heat-processed food. Due to its widespread occurrence and strong carcinogenicity in food and beverages, 4-MEI has received attention from regulatory organizations and consumers. Some studies have reported the occurrence and exposure of 4-MEI in food, but few studies have involved traditional tea beverages, which is related to the limited analytical methods currently being influenced by complex tea matrices. For this issue, this study presents a simple, reliable, and highly sensitive analytical method for the determination of 4-MEI in tea using liquid chromatography–high resolution mass spectrometry. By means of this method, a total of 570 tea samples from typical tea-producing regions in China were monitored for contamination of 4-MEI. The results showed that the average 4-MEI level (136 μg/kg) in oolong tea was significantly higher than that in other types of tea samples. Based on contamination levels and tea consumption data in China, the daily intake doses (0.04–1.16 μg/day) of 4-MEI among tea consumers were obtained. As a result, the health risk of Chinese tea consumers consuming 4-MEI alone through tea consumption is relatively low, but the overall intake level of 4-MEI in other foods cannot be ignored.